Engagement in marriage according to the Reusam of Kampung Tanjung Keramat Number 1 of 2018 in the review of maqashid sharia - Yasin Bayla; Muhammad Nasir (International Journal of Sharia Studies, 2023)
This article aims to review the effectiveness of reusam using the maqashid al-syari’ah analysis knife. Engagement in the Indonesian Malay community tradition is a follow-up to a series of proposals (al-khitbah), where both parties, the prospective bride and groom, make promises within a specific time limit until the marriage contract is carried out. The phenomenon that is developing for prospective brides and grooms who are getting engaged, among other things, is that a close relationship has occurred, even as if they were already married, where the intensity of the relationship between the prospective bride and groom is very intimate and pregnancies often occur before marriage. To overcome this problem, the village government and community leaders carried out control by issuing village-level regulations called Reusam. Through Reusam Number 1 of 2018 in Tanjung Keramat Village, the time limit for engagement and marriage has been set to a maximum of 2 months to overcome the engagement’s negative impact.